Pelaksanaan Ijab Kabul Pernikahan di Masa Pandemi Covid-19 di KUA Kecamatan Sampang Madura - Dakwatul Chairah (AL-HUKAMA: The Indonesian Journal of Islamic Family Law, 2021)
This study aims to determine the implementation of the ijab kabul during the Covid-19 pandemic at the KUA, Sampang District, where there seems to be a change in the legal behavior of the community, where the Ijab and Kabul must be continuous and comply with health protocols. The method used is descriptive qualitative, which describes and studies in depth the practice of ijab and kabul at the KUA in Sampang District and then analyzes it based on the perspective of Islamic law or fiqh. This study found that, KUA Sampang District, Sampang Madura Regency issued a new procedure in the marriage contract. In the implementation of the Ijab and Kabul, the Penghulu as the representative of the female guardian performs ageppak bumih (clapping hands to the earth) after saying the Ijab so that the prospective groom immediately answers (kabul) the consent that was said by the Penghulu. They view that the marriage contract must be carried out in one assembly, where the ijab must be continuous with the kabul. In the implementation of the ijab kabul, the headmaster and the groom face each other, are about one meter apart, and do not shake hands. The penghulu claps his hands to the earth to remind the groom to immediately say Kabul, because there should be no time lag between ijab and kabul. This does not cause the marriage contract to be canceled, because ageppak bumih is an act of reminding the groom to immediately pronounce his kabul, answer the consent of the penghulu and so that the marriage contract remains valid.